"Buslish" in East and Southeast Asian business – a role for continuing education. Issue 2 (23rd February 2022) - Foster, Morris John; Richardson, Christopher
Abstract : Purpose: The aim of the research, in the East and Southeast Asia context, is to explore the advantages and problems of Buslish (business facilitation English) for managers and to generate suggestions for maximising the use of Buslish as a critical resource in organisational effectiveness, including potential educational support and its required technology. Design/methodology/approach: Data aimed to explore the issue were collected from a multi-country sample of 31 non-native English speakers, using a semi-structured questionnaire, plus in-depth interviews (10) with some respondents. Data were analysed using a mixture of descriptive statistics and logical argumentation. Findings: The authors found a strong agreement that Buslish is important in the chosen setting, but there are problems in practice. Views on the importance of style and precision of the language actually used varied considerably. A key practical implication is that there is a role for English continuing professional development (CPD) courses. Practical implications: Firms should support the development of English language skills of employees, certainly at management level and perhaps also at shop floor level. Suitable courses could be offered in firms' CPD programmes. Employees who are native speakers should be encouraged to enunciate clearly for non-native speaker colleagues, not to use slang and not to speak too quickly. While the authors encourage the use of contemporary communication technologies (e.g. virtual classrooms), they maintain that these should be supplementary in nature, supporting, rather than replacing, face-to-face learning formats. Originality/value: A key aspect of the originality of the work is derived from the specific location, primary data collected and the creative nexus of the initial issue and its educational requirements, including technologies.